2017
DOI: 10.3389/fphar.2017.00622
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity and Toxicological Assessment of Curcumin PLGA-Encapsulated Nanoparticles

Abstract: Curcumin is a polyphenolic pigment isolated from the rhizomes of Curcuma longa (turmeric), a medicinal plant widely used in the ancient Indian and Chinese medicine. The antiplasmodial activity of curcumin is often hampered by its fast metabolism and poor water solubility, thus its incorporation into a delivery system could circumvent this problem. This study aimed to evaluate the in vivo antiplasmodial activity and the toxicity assessment of curcumin incorporated into poly (lactic-co-glycolic) acid (PLGA) nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Curcumin-artesunate PLGA entrapped nanoparticle (CA-PLGA) was formulated by solvent evaporation from oil-in-water single emulsion method as described by Busari et al ( 2017 ). Briefly, 5 mg each of curcumin and artesunate was added to an organic phase containing homogenous solution of 50 mg PLGA in 3.5 mL of dichloromethane and 0.5 mL of acetone to constitute 1:5 (drugs to PLGA) ratios.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin-artesunate PLGA entrapped nanoparticle (CA-PLGA) was formulated by solvent evaporation from oil-in-water single emulsion method as described by Busari et al ( 2017 ). Briefly, 5 mg each of curcumin and artesunate was added to an organic phase containing homogenous solution of 50 mg PLGA in 3.5 mL of dichloromethane and 0.5 mL of acetone to constitute 1:5 (drugs to PLGA) ratios.…”
Section: Methodsmentioning
confidence: 99%
“…CA-PLGA nanoparticle diameter, zeta potential and polydispersity index (PDI) were measured by dynamic light scattering (DLS) method using Zetasizer Nano-ZS (Malvern Instruments, UK) as previously described (Busari et al, 2017 ; Dauda et al, 2017 ). The size and PDI of CA-PLGA nanoformulation were determined from nanoparticle suspension of appropriate amount of the drug loaded nanoparticles dispersed in MQ water in a clear disposable sizing cuvette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these drug carriers, poly-lactic-co-glycolic acid (PLGA) microspheres become a preferred choice for its favorable stability, low toxicity, and high encapsulation efficiency for hydrophobic agents. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (CURC), derived from the plant Curcuma longa, is a bioactive component of turmeric with the ability to modulate the immune system [13]. Although curcumin has poor water solubility and low bioavailability and stability, some studies have confirmed that drug carriers such as proteins, polymeric particles, and polylactic-glycolic acid copolymer (PLGA) microspheres can effectively solve this problem and give full play to its antioxidant, anti-inflammatory, and anti-hyperglycemic properties [14][15][16][17][18]. Natural or chemically modified curcumin could upregulate insulin sensitivity and reduce glucose and glycosylated hemoglobin levels, which has great potential as an alternative therapeutic option for diabetes mellitus and its complications [19,20].…”
Section: Introductionmentioning
confidence: 99%